Timing of expression of inflammatory mediators in skeletal muscles from mice acutely infected with the RA strain of Trypanosoma cruzi - Cutrullis, Romina Andrea (2009)
Fil: Cutrullis, Romina Andrea. Servicio de Parasitología y Chagas, Hospital de Niños Dr. Ricardo Gutiérrez; Argentina.